Bioelectronics‐Related 2D Materials Beyond Graphene: Fundamentals, Properties, and Applications. (6th September 2020) - Wang, Bolun; Sun, Yufei; Ding, Hanyuan; Zhao, Xuan; Zhang, Lei; Bai, Jingwei; Liu, Kai
Abstract: The rapid development of bioelectronics has lead to the emergence of versatile biorelated architectures for information processing systems, sensors, actuators, and wearable devices. In recent years, 2D materials beyond graphene have been demonstrated to be essential bioelectronic device components owing to their merits of atomic thickness, high transparency, large specific area, unique electrical/optical properties, and good biocompatibility. Herein, the recent advances in the bioelectronic applications of 2D materials beyond graphene are reviewed and their physicochemical properties, biocompatibility, synthesis, and processing methods are described. Moreover, the design strategies, working mechanisms, and performances of various bioelectronic devices based on these materials are summarized and the perspectives and challenges of this research field are highlighted. Thus, this review is expected to inspire new insights and technical advances for future research. Abstract : 2D materials beyond graphene are essential components of bioelectronic devices, showing the merits of atomic thickness, high transparency, large specific area, unique electrical/optical properties, and good biocompatibility. This review summarizes the recent advances in the bioelectronic applications of 2D materials beyond graphene from the viewpoint of fundamental research and device development.